Fundamentals and applications of micro and nanofibers - Yarin, Alexander L., 1953-; Pourdeyhimi, Behnam; Ramakrishna, Seeram (Cambridge : Cambridge University Press, 2014)
A comprehensive exposition of micro and nanofiber forming, this text provides a unified framework of all these processes (melt and solution blowing, electrospinning, and so on) and describes their foundations, development and applications. It provides an up-to-date, in-depth physical and mathematical treatment, and discusses a wide variety of applications in different fields, including nonwovens, energy, healthcare and the military. It further highlights the challenges and outstanding issues from an interdisciplinary perspective of science and technology, incorporating both fundamentals and applications. Ideal for researchers, engineers and graduate students interested in the formation of micro and nanofibers and their use in functional smart materials.
Polymer physics and rheology -- General quasi-one-dimensional equations of dynamics of free liquid jets. Capillary and bending instability -- Melt- and solution blowing -- Electrospinning of micro- and nanofibers -- Additional methods and materials used to form micro- and nanofibers -- Tensile properties of micro- and nanofibers -- Post-processing -- Applications of micro- and nanofibers -- Military applications of micro- and nanofibers -- Applications of micro- and nanofibers and micro- and nanoparticles: healthcare, nutrition, drug delivery and personal care.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Textile fibers, Synthetic; Nanofibers; Electrospinning